2018
DOI: 10.1029/2018jg004657
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear Trends in Solute Concentrations and Fluxes From a Suburban Watershed: Evaluating Effects of 100‐Year Flood Events

Abstract: Anthropogenic activities have increased solute concentrations and fluxes in rivers globally.Increases in salt, dissolved organic carbon, and inorganic nutrients have been attributed to changes in atmospheric deposition, road salt and fertilizer application, and urbanization. Extremely large flood events, which are increasing in frequency and duration, could also alter river chemistry by flushing various solute reservoirs within watersheds and effectively "resetting" the linkages between land and river. We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…In our long‐term study site the Lamprey River, for example, a dilution and flushing response of NO 3 − to several specific storms has been reported (Carey et al, 2014) and NO 3 − c‐Q has been shown to be chemostatic with no variation across seasons when considering storms throughout the year (Koenig et al, 2017). Additionally, long‐term weekly grab samples at the Lamprey River also showed chemostatic NO 3 − c‐Q (Coble et al, 2018), whereas in fact the use of continuously operating sensors throughout the year shows that c‐Q behavior is predominantly source limited but can also be both chemostatic and transport limited for some of the year. Use of annual data sets, whether from weekly sampling or aggregation of sensor analyses, is thus often likely to result in the conclusion that a system is chemostatic because the embedded variation that occurs at shorter time scales is lost when aggregating data at the annual scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our long‐term study site the Lamprey River, for example, a dilution and flushing response of NO 3 − to several specific storms has been reported (Carey et al, 2014) and NO 3 − c‐Q has been shown to be chemostatic with no variation across seasons when considering storms throughout the year (Koenig et al, 2017). Additionally, long‐term weekly grab samples at the Lamprey River also showed chemostatic NO 3 − c‐Q (Coble et al, 2018), whereas in fact the use of continuously operating sensors throughout the year shows that c‐Q behavior is predominantly source limited but can also be both chemostatic and transport limited for some of the year. Use of annual data sets, whether from weekly sampling or aggregation of sensor analyses, is thus often likely to result in the conclusion that a system is chemostatic because the embedded variation that occurs at shorter time scales is lost when aggregating data at the annual scale.…”
Section: Discussionmentioning
confidence: 99%
“…Human‐influenced watersheds can transition from chemodynamic to chemostatic solute‐discharge relationships when assessed using long‐term analyses (Coble et al, 2018; Duncan et al, 2017; Dupas et al, 2016). Both mainstem rivers drain predominantly forested but urbanizing watersheds and patterns of NO 3 − c‐Q behavior reflect characteristics of both forested and impacted tributaries.…”
Section: Discussionmentioning
confidence: 99%
“…estuary. In doing so, the data set captures continued changes in landuse and land-cover, population density and impervious cover (Coble et al, 2019), changing seasonality (Contosta et al, 2017), and multiple extreme events including two one-hundred-year scale floods (Coble et al, 2018). A compilation of associated publications using these long-term data can be found in Table 3.…”
Section: Long-term Data (20 Years)mentioning
confidence: 99%
“…Although the watershed remains heavily forested (73%), it is characterized as suburban and a mixed land-use environment incorporating agriculture (5%), development (7%) and wetlands (10%; NOAA Coastal Change Analysis Program, 2016). Human population has been increasing by 0.45 people km −2 year −1 since 1990 (60 people km −2 in 2020) with housing density at 25 housing units km −2 (Coble et al, 2018). A vast majority of the watershed's population utilizes on-site waste disposal (i.e., septic systems; Trowbridge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach has been used to understand the various controls on solutes and sediments across diverse environments (e.g., Johnson et al, 1969;Godsey et al, 2009;Herndon et al, 2018;Rose et al, 2018;Wymore et al, 2019), less attention has been given to the mobilization and transport of N and the implications for N cycling processes. And while certain forms of dissolved N (e.g., NO − 3 , DON) often do not appear to respond to changes in discharge across a broad range of flow conditions (Wymore et al, 2017;Coble et al, 2018), concentrations of NO − 3 do respond to changes in flow during individual storm events (Koenig et al, 2017a;Bernal et al, 2019) even when the overall relationship between concentration and discharge is weak. A detailed examination of how the different forms of dissolved N respond to changes in flow across diverse environments would help to elucidate the relative contribution Under elevated runoff, sediment concentrations increase due to the activation of addition flow paths and sources from the hillslope and watershed.…”
Section: Eq 3: How Do Concentrations and Fluxes Of Nitrogen Respond Tmentioning
confidence: 99%